Students’ Needs, Perceptions, and Challenges in AI-Supported Pre-Speaking Preparation - Meidy Kautsar Arriv; Fadliyah Uzma (Universitas Islam Negeri Palopo, 2026)
Pre-speaking preparation enables English as a foreign language (EFL) learners to plan ideas, select vocabulary, and manage confidence before oral performance. This study explored Grade 9 students’ needs, perceptions, and challenges regarding the use of artificial intelligence (AI)-based tools during pre-speaking preparation. A descriptive qualitative design was employed with 19 students in one class at a school in Bekasi. Data were collected through a 15-item five-point Likert-scale questionnaire, classroom observations, and interviews with two students. Questionnaire responses were summarized using percentages, while the interview and observation data were used to support interpretation. The findings showed that 80%-85% of the students agreed that they needed additional preparation time, help organizing ideas, vocabulary support, and more practice opportunities. Between 85% and 90% viewed AI positively for idea generation, vocabulary development, content organization, confidence, and practice before class. However, 55% found some AI-generated answers difficult to understand, and 80% still emphasized the need for teacher guidance. The interviews also identified slow internet connectivity and responses that did not always match students’ expectations. AI can therefore function as a complementary scaffold in pre-speaking preparation, but its use should remain teacher-guided and appropriate to learners’ language level.